Penerapan Nilai-nilai Pancasila melalui Projek Penguatan Profil Pelajar Pancasila: Studi Kasus di SMAN 5 Sukabumi (Jurnal Sosial Humaniora dan Pendidikan, 2025)
In the era of globalization and rapid technological development, strengthening the values of Pancasila among students has become a significant challenge. The strong influence of foreign cultures and the declining awareness of national identity have highlighted the need for new approaches in character education. To address these challenges, the Projek Penguatan Profil Pelajar Pancasila (P5), or the Project to Strengthen the Profile of Pancasila Students, was introduced as an interdisciplinary and co-curricular learning initiative. This project aims to equip students with the ability to observe and find solutions to problems in their surrounding environment. This study aims to examine how the P5 project is implemented at SMAN 5 Sukabumi and to identify the supporting and inhibiting factors in its implementation. A qualitative approach was employed using a case study method. Data collection techniques included interviews, observations, and documentation. The collected data were analyzed through three stages: data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of P5 at SMAN 5 Sukabumi is carried out through three main stages: planning, implementation, and evaluation. The themes raised in the project include "The Voice of Democracy," "Unity in Diversity" (Bhinneka Tunggal Ika), and "Sustainable Lifestyle." Supporting factors for this project include parental support, the utilization of information technology, the availability of adequate facilities and infrastructure, and community involvement. On the other hand, the obstacles faced include the lack of discipline among some students during the activities and the fact that some teachers have not yet fully understood the implementation flow of the P5 project.